Impacted permanent maxillary incisors - clinical and therapeutic considerations - Mioara Decusară; Daniela Cornea; Cerasella-Dorina Șincar (Amaltea Medical Publishing House, 2019)
The frequency of impactation of the maxillary permanent incisors is low in dental practice, the orthodontist having the duty to determine the cause and establish and apply an orthodontic treatment as early as possible. The diagnosis of certainty of impactation of the permanent maxillary incisors is established when there is a delay in their eruption for about one year after the exfoliation of milky teeth. The interceptive and curative orthodontic treatment is important for facial aesthetics, for harmonious facial and skeletal development, for correcting possible malfunctions (phoniatric, masticatory, deglutition).